PENERAPAN MEDIA VIDEO ANIMASI DENGAN METODE INQUIRY DALAM PEMBELAJARAN MERINGKAS TEKS CERITA LEGENDA PADA KELAS VIII SMP IT DAARUT TAHFIDZ KARANGASEM KABUPATEN DEMAK TAHUN AJARAN 2020 - Wibawanti, Luluk; Alfiah, Alfiah; Sunaryo, Sunaryo (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2021)
This research is motivated by the lack of vocabulary that is known by students and the lack of media and learning methods so that the learning process becomes boring. The problem in this study is how the results of the application of video animation media with the inquiry method in summarizing the legend story text in class VIII SMP IT Daarut Tahfidz Karangasem, Demak Regency? The purpose of this study is to describe the application of animated video media with the inquiry method in summarizing the legendary text of the class VIII SMP IT Daarut Tahfidz Karangasem in the academic year of 2020. This study used a qualitative descriptive method. The results of the study based on the test scores show different percentages. Of the 28 students there is 1 student or 4% who have not completed and 27 students or 96% have completed. The class average score of the results of the test was 80.65. This value has reached the school's KKM score of 70.Thus, animated video media with the inquiry method in learning summarizes the legendary story text in class VIII SMP IT Daarut Tahfidz Karangasem, Demak Regency, 2020 academic year.